Synthesis and intramolecular cyclization of novel beta,beta-bis(benzo[b]thienyl)dehydroalanine derivatives - Abreu, Ana S. (2003)
The methyl ester of tert-butyloxycarbonyl-beta,beta-dibromodehydroalanine was obtained in a one pot procedure from bis-(N-tert-butyloxycarbonyl)dehydroalanine. The former was reacted with several boronic benzo[b]thiophene acids under Suzuki cross coupling conditions, to give new beta,beta-bis-(benzo[b]thienyl)dehydroalanines in high yields. These compounds were cyclized to pyrrole derivatives by treatment with Pd(OAc)2 and Cu(OAc)2 in DMF.